The problem of the inverse Lyapunov exponent and its applications - Lawnik, Marcin (Nonlinear Analysis: Modelling and Control, 2018)
The problem of the inverse Lyapunov exponent was formulated and solved, involving to find such chaotic transformation for which the value of the Lyapunov exponent is given in advance. The solution procedure was presented by a numerical example. Furthermore, applications of the discussed model in chaos based cryptography were discussed.